Strategic alliances are an introduction to dealing with strategic shocks: A study of the opinions of a sample of the administrative leadership of contracting companies operating in the city of Mosul (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to clarify the influence exerted by strategic alliances and its dimensions represented by (value chain partnership, licensing arrangement, joint projects, mutual service union) on strategic shocks and its dimensions represented by (the industrial environment factor (exchange rate fluctuation), the institutional environmental factor (Soft budget constraints are offset by hard one), the company's capabilities (low versus high leverage) and the relationship between them, and the researched field was the contracting companies operating in the city of Mosul (listed within the Iraqi Contractors Union/Ninawa branch), which were chosen to conduct the applied aspect of the research, and the electronic questionnaire was distributed to The researched field was conducted via the WhatsApp application for contractors working in the city of Mosul, and (98) responses were obtained via the electronic link prepared for this purpose. The research community consisted of general managers of contracting companies. The descriptive analytical approach was adopted in the research, and statistical software (spss) was employed. v.27) for statistical analysis of the collected data, and the most prominent results were the presence of an inverse relationship between both strategic alliances and strategic shocks, and there is also a significant effect between strategic alliances on strategic shocks.